2017
DOI: 10.1371/journal.pntd.0005493
|View full text |Cite
|
Sign up to set email alerts
|

Development of a glycoconjugate vaccine to prevent invasive Salmonella Typhimurium infections in sub-Saharan Africa

Abstract: Invasive infections associated with non-typhoidal Salmonella (NTS) serovars Enteritidis (SE), Typhimurium (STm) and monophasic variant 1,4,[5],12:i:- are a major health problem in infants and young children in sub-Saharan Africa, and currently, there are no approved human NTS vaccines. NTS O-polysaccharides and flagellin proteins are protective antigens in animal models of invasive NTS infection. Conjugates of SE core and O-polysaccharide (COPS) chemically linked to SE flagellin have enhanced the anti-COPS imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 52 publications
(59 reference statements)
3
81
0
Order By: Relevance
“…[23] In addition, it has been shown that antibody binding can alter the conformations sampled by an oligosaccharide, which may further facilitate binding. [24,46] For an O1 OPS vaccine, despite the reduced accessibility of the β-D-Galf and α-D-Galp linear backbone monosaccharides in the RUs of D-Gal-III OPS, antibodies induced against the terminal Gal-II region should be similarly efficacious in the context of D-Dal-I or D-Gal-III given the relative insensitivity of D-Gal-II to the presence of the branches. In addition, as the Gal-II region is membrane distal, it is expected that it would be more exposed compared to the membrane proximal D-Gal-I/D-Gal-III in O1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] In addition, it has been shown that antibody binding can alter the conformations sampled by an oligosaccharide, which may further facilitate binding. [24,46] For an O1 OPS vaccine, despite the reduced accessibility of the β-D-Galf and α-D-Galp linear backbone monosaccharides in the RUs of D-Gal-III OPS, antibodies induced against the terminal Gal-II region should be similarly efficacious in the context of D-Dal-I or D-Gal-III given the relative insensitivity of D-Gal-II to the presence of the branches. In addition, as the Gal-II region is membrane distal, it is expected that it would be more exposed compared to the membrane proximal D-Gal-I/D-Gal-III in O1.…”
Section: Resultsmentioning
confidence: 99%
“…Results are averaged over the entire HREST2-bpCMAP trajectories.Glycosidic linkage-based clustering analysis (GL): Additional analysis was undertaken to obtain a more quantitative estimate of the conformational states being sampled by the two OPS. Conformations of the saccharides were identified based on clustering of glycosidic linkages (GL) and their sampled populations determined, as previously presented [18,23,24,46]. To perform GL clustering it is necessary to assign the different glycosidic conformations to integers on which the clustering is performed.…”
mentioning
confidence: 99%
“…Typhimurium glycoconjugate vaccine using wzzB ‐controlled OPS antigen haptens, proof that this strategy is effective (Baliban et al . ). Salmonella Typhimurium overexpressing wzzB produced a single high molecular weight species of O‐polysaccharide as measured by HPLC‐SEC.…”
Section: Discussionmentioning
confidence: 97%
“…1.5% bacteriological agar (AmericanBio, MA) was added to HS for solid media preparations. Fully chemically defined medium (CDM) used for growth of KP in fermentation cultures and to assess guanine auxotrophy has been described previously [ 19 ]. 0.004%-0.025% guanine (Sigma Aldrich, MO) was added for the growth of CVD 3001 to supplement the guaBA mutation.…”
Section: Methodsmentioning
confidence: 99%
“…KP O1, O2, O3 and O5 reagent strains were grown in 4 L fermentation cultures in a BioStat A+ fermenter (0.6–5 L working volume, 6.6 L total volume) (Sartorius, Germany) essentially as described [ 19 ]. Briefly, 5–10 colonies were selected from an HS agar plate grown overnight at 37°C and used to inoculate a 250 mL shake flask containing 50 mL of CDM (supplemented with 0.025% guanine for CVD 3001).…”
Section: Methodsmentioning
confidence: 99%